2018
DOI: 10.3389/fphys.2018.01641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Exercise on Advanced Glycation End Products Levels in Patients Living With the Human Immunodeficiency Virus

Abstract: Introduction: Combined antiretroviral therapy (cART) used to treat acquired immunodeficiency virus (HIV) induces a number of adverse effects, such as insulin resistance and dyslipidemia, which ultimately increases the cardiovascular risk. Advanced glycation end products (AGEs) have been implicated in the etiology of cardiovascular diseases, diabetes and other chronic diseases. It is known that physical exercise improves the lipid profile, insulin resistance and reduces the risk of cardiovascular diseases. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
(47 reference statements)
1
22
0
Order By: Relevance
“…In Maputo, a prior study showed that women under cART increased their overall physical fitness in response to a 13-week aerobic and strength training program ( 35 ). In Rio de Janeiro, a structured multimodal program has been consistently shown to improve physical fitness, body image, and quality of life of low SES patients of both sexes, while preserving their immune function ( 36 , 37 ) and reducing the cardiovascular risk ( 38 , 39 ). However, strategies available in the literature are several, and even unorthodox approaches to increase the access of PLHIV to PA produced promising results.…”
Section: Discussionmentioning
confidence: 99%
“…In Maputo, a prior study showed that women under cART increased their overall physical fitness in response to a 13-week aerobic and strength training program ( 35 ). In Rio de Janeiro, a structured multimodal program has been consistently shown to improve physical fitness, body image, and quality of life of low SES patients of both sexes, while preserving their immune function ( 36 , 37 ) and reducing the cardiovascular risk ( 38 , 39 ). However, strategies available in the literature are several, and even unorthodox approaches to increase the access of PLHIV to PA produced promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that even patients with chronic diseases showed a marked reduction in AGEs serum level following PE. KL Rodrigues et al reported improved AGEs serum level among physically inactive HIV-patients following three supervised PE programs [44]. Furthermore, Sheikholeslami-Vatani illustrated a signifi cant reduction in AGEs level among postmenopausal women with type II DM aft er conducting eight weeks of supervised resistant PE three times a week [45].…”
Section: Evidence Of the Regular Physical Exercise Effect On Advanced Glycated End-productsmentioning
confidence: 99%
“…3 In their letter, Kotani and Gugliucci searched and compiled data from interventional studies in which the effects of physical exercise on AGEs and soluble AGEs receptors (sRAGE) were evaluated. [4][5][6][7][8][9][10] Based on those studies, the authors concluded that the practice of physical exercise could reduce serum AGEs and, seemingly contradictory, it also reduces sRAGE concentrations. 1 However, we would advert caution before drawing these conclusions.…”
Section: Dear Editormentioning
confidence: 99%
“…[13][14][15][16] Moreover, three studies included participants with type 1 9 and type 2 8 diabetes and patients living with human immunodeficiency virus. 10 Both hyperglycemia and elevated oxidative stress are complications related to these diseases and, in turn, can increase endogenous AGEs formation. 17 Second, medication use may also affect AGEs and sRAGE concentrations.…”
Section: Dear Editormentioning
confidence: 99%